Influence of moieties on morphology, thermal, and dielectric properties in polyamide‐polyhedral oligomeric silsequioxanes nanocomposites. Issue 8 (29th November 2012) - Gnanasekaran, D.; Walter, P. Ajit; Reddy, B.S.R.
Abstract A series of new hexafluoroisopropylidene, isopropylidene, carbonyl, and ether moieties substituted polyamides have been prepared from aromatic diamines and various moieties substituted aromatic dianhydrides. The synthesized polyamides were readily soluble in polar solvents such as N‐methyl‐2‐pyrrolidone, N, N‐dimethylacetamide, N, N‐dimethylformamide, and dimethyl sulfoxide. These polyamides exhibited good thermal stability and high char yields. The chemical and physical properties of the newly prepared polyamide‐polyhedral oligomeric silsequioxanes (PA‐POSS) were compared in terms of their chemical structures and thermal properties. The morphological properties of the polymeric nanocomposites depend both on their chemical structure of dianhydride and the aggregation of POSS were investigated by scanning electron microscopy, transmission electron microscopy, and atomic force microscopy. Polyamides with bulky POSS and ﬂuoro groups can effectively decrease dielectric constants. The dielectric constants of PA‐POSS were found to be decreased from 3.75 to 3.29 by changing the substitution. These polyamides showed good thermal stability up to 353 °C for a 10 % weight loss. The fluorinated polyamides have relatively higher thermal stability than the polyamides without halogen because of high bond energy of CF bond. The fiuorinated groups in the polymer backbone have played an important role in the improvement of dielectric performance of polymers. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers